Risk interrelationship among multiple primary tumors: A case report and review of literature. Issue 15 (April 2018) - Safi, Mohammed; Sun, Xiuhua; Wang, Lifen; Zhang, Xinwei; Song, Jicheng; Ameen, Mohammed
Abstract: Rationale: Along with advanced management in oncology, great progress has been recently achieved in the studies of multiple primary tumors. Several reports have studied the coexistence between lymphoma and either renal cell carcinoma (RCC) or Warthin tumor. However, the level of coexistence between these cases remains unclear due to the absence of a distinct link between them. Patient concerns: We present a unique case of multiple primary tumors (lymphoma, RCC, and Warthin tumor) in an 80-year-old man and a review of the literature on the coexistence of RCC with lymphoma and lymphoma with Warthin tumor. Diagnosis: With a history of RCC, the patient had a freely movable lump under his left ear, and the pathological report indicated Hodgkin lymphoma and Warthin tumor. Intervention: RCC and Warthin tumor of the patient were surgically treated, followed by 2 cycles (14 days per cycle) of Epirubicin 40 mg day 1, Bleomycin 8 mg day 1, Vincristine 2 mg day 1, and Dacarbazine 500 mg day 1. The chemotherapy protocol was then changed to Epirubicin 40 mg day 1, Vincristine 2 mg day 1, and Dacarbazine 500 mg day 1 for 7 cycles. Outcomes: After the last day of chemotherapy, the patient showed a complete response. Lessons: To the best of our knowledge, this paper is the first to report a case of multiple primary tumors with a complete response. For their early detection, favorable prognosis, and correlation identification, we suggest a transitive relation between these coexisting tumors. Therefore, similar studies should be conducted.